TES PRODUKTIF BERBAHASA - Anggraini, Nani (Lentera: Jurnal Ilmiah Kependidikan, 2017)
This paper discusses the relationship of active productive language competence. Language-productive activity is the activity of conveying ideas, messages, or information by the speaker. Productive competence test is aimed to ask learners in language work, to do something through language. In this productive competency test, the learners do not just choose, create, and construct a language, but also choose, create, and construct what will be uttered through the language. This writing is prepared with the aim to be used as a reference and theoretical basis to formulate and to judge on productive language competence test.